2011
DOI: 10.4103/0256-4947.84629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of neoadjuvant chemotherapy with platinum-based regimen for patients with locoregionally advanced head and neck squamous cell carcinoma: an evidence-based meta-analysis

Abstract: BACKGROUND AND OBJECTIVES:As a vital chemotherapeutic modality, the clinical benefits of neoadjuvant chemotherapy still remain uncertain and controversial. The purpose of this meta-analysis was to evaluate the efficacy of neoadjuvant chemotherapy with a platinum-based regimen for patients with locoregional stage III or IV squamous cell carcinoma of the head and neck.DESIGN AND SETTING:Meta-analysis of randomized, controlled trials.METHODS:Relevant randomized controlled trials (RCTs) were identified through sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Out of these 214 reports, 21 reviews were considered potentially eligible and full text reports of 21 reviews were retrieved and reviewed. Ten reviews with pooled analysis [2, 3, 916] were identified as potentially relevant to the topic areas covered by this guideline. Three reports focused on induction chemotherapy, two on postoperative chemotherapy, two on targeted agents, one on concurrent chemotherapy and in two reports, the timing of chemotherapy not specified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of these 214 reports, 21 reviews were considered potentially eligible and full text reports of 21 reviews were retrieved and reviewed. Ten reviews with pooled analysis [2, 3, 916] were identified as potentially relevant to the topic areas covered by this guideline. Three reports focused on induction chemotherapy, two on postoperative chemotherapy, two on targeted agents, one on concurrent chemotherapy and in two reports, the timing of chemotherapy not specified.…”
Section: Resultsmentioning
confidence: 99%
“…After full text review, five meta-analyses [24, 1416] were included. Four [9–11, 13] were excluded because they reviewed RCTs of non-LASCCHN, and one meta-analysis [12] was excluded following AMSTAR assessment. No further discussions of these references will be made in this guideline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Neoadjuvant chemotherapy (NACT) has a significant role in the comprehensive treatment of hypopharyngeal carcinoma (HPC). 4 The response evaluation criteria for solid tumors (RECIST) 1.1 are commonly used to assess tumor response to the treatment for HPC by evaluating tumor load changes based on a dimensional measurement. 5 However, due to the complexity of the anatomic location and mucosal spread of HPC, where the tumor often has complex shapes and irregular margins, the long dimension cannot always be accurately measured by evaluators.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of head and neck cancer patients has slightly improved following the use local therapies, such as surgery or radiotherapy, in large part due to locoregional and distant metastatic failure [10]. While, systemic monotherapy using platinum based compounds have limited response rates except when combined with radiotherapy [1114]. Whereas, targeted systemic therapy with monoclonal antibodies lacks the potency necessary to completely halt tumorigenesis resulting in varied response rates and limited improvement in survival rates [15].…”
Section: Introductionmentioning
confidence: 99%